2009
DOI: 10.1530/rep-08-0320
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor signaling in hen ovarian granulosa cells is dependent on stage of follicle maturation

Abstract: The recent identification of toll-like receptor (TLR) signaling within ovarian granulosa cells has broad implications for ovarian physiology. Functions of TLRs within granulosa cells of the laying hen are of particular interest due to the method of transovarian transmission of Salmonella enteritidis, which results in egg contamination. This study utilized hen granulosa cells to evaluate the expression and function of Gallus TLR-signaling at distinct stages of follicular maturity. Data presented herein demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 45 publications
5
23
0
3
Order By: Relevance
“…Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs. In hens, it has been reported that the oviduct, as well as ovarian follicular and stromal cells, expresses TLRs, AvBDs, as well as proinflammatory cytokines and chemokines, and the expression of these molecules was upregulated by LPS stimulation (Subedi et al 2007, Abdel Mageed et al 2008, Ozoe et al 2009, Woods et al 2009, Abdelsalam et al 2011, Nii et al 2011. Similar to the female reproductive tract, the gene expression data presented in this study revealed that rooster SCs responded to LPS stimulation.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs. In hens, it has been reported that the oviduct, as well as ovarian follicular and stromal cells, expresses TLRs, AvBDs, as well as proinflammatory cytokines and chemokines, and the expression of these molecules was upregulated by LPS stimulation (Subedi et al 2007, Abdel Mageed et al 2008, Ozoe et al 2009, Woods et al 2009, Abdelsalam et al 2011, Nii et al 2011. Similar to the female reproductive tract, the gene expression data presented in this study revealed that rooster SCs responded to LPS stimulation.…”
Section: Discussionsupporting
confidence: 59%
“…Intravenous LPS injection may mimic the effects of such bacterial invasion into ovarian tissues. It has been reported that TLR4, which is used to recognize LPS of gram-negative bacteria, is expressed in the granulosa and theca layers (Subedi et al, 2007;Woods et al, 2009). The upregulation of IL-1β, IL-6, and CXCLi2 expression by LPS in the current study could probably be initiated by the interaction of LPS and TLR4 in ovarian tissues.…”
Section: Figurementioning
confidence: 53%
“…Previous reports identified antigen-presenting cells, T and B cells in the follicles that showed unique changes in density affected by age and estrogen (Barua et al, 1998(Barua et al, , 2001; Barua and Yoshimura, 1999). The expression of toll-like receptors, a class of pattern recognition receptors responsible for initiation of the innate immune response, has also been identified in the theca and granulosa layers (Subedi et al, 2007;Woods et al, 2009). Furthermore, the synthesis of avian β-defensins, antimicrobial peptides, in the follicular wall has also been reported (Subedi et al, 2007(Subedi et al, , 2008Abdelsalam et al, 2010;Michailidis et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Activation of TLR signaling occurs following recognition and interaction with conserved small molecular sequences found on the surface of invading pathogens, as well as some endogenous molecules. In animal models of ovarian function, TLRs present on granulosa cells have been implicated in ovulation, a naturally occurring inflammatory-like response [5; 9; 10]. In models of OSE-derived cancer, cancerous human OSE cell lines have also been shown to express multiple TLRs [6; 11].…”
mentioning
confidence: 99%